(untitled) (Al Basirah, 2020)
In the modern world, the issues and challenges between the capitalist and labor relation have been worth importance from last many years. Practically speaking, ensuring the rights and obligations of both parties can eradicate the distances between the two potential economic players. Explicit clauses of contract can build the confidence level of labor and capital as well which will further stimulate the level of productivity in the country rather it will serve as catalyst for the sustainable development. The Golden means for the capitalist and labor has been highlighted which stem form the foundation laid down in Quran and Hadiths. The maximum clarity in the job contract and assurance of the rights and obligations of the Capitalist and Labor under the umbrella of Islamic Jurisprudence can only enhance the healthy and growth oriented environment for all the economic activities. The main stance of the Islam Golden means is interest of one party must not be escalated on the cost of other party.